2015
DOI: 10.1186/s12957-015-0522-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the standardized uptake value of 18F-FDG PET/CT and the prognostic factors of invasive lobular carcinoma: in comparison with invasive ductal carcinoma

Abstract: BackgroundThe aims of this study were to evaluate the associations between the maximum standardized uptake value (SUVmax) and prognostic factors in invasive lobular carcinoma (ILC) and to compare these results with those in invasive ductal carcinoma (IDC).MethodsThe study included pathologically confirmed ILCs (n = 32) and IDCs (n = 73). We retrospectively evaluated the preoperative 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and measured the SUVmax. The pathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Furthermore, significant correlations between tumour size and the size of metastatic axillary LNs, SUV max -T and size of metastatic axillary LNs, SUV max -T and SUV max -LN were found in our LABC group. Primary tumour size was stated to be predictive of metastatic involvement of axillary LNs [33], SUV max -T was reported to increase with tumor grade [15, 17, 39] and strong relationships were found among SUV max values, BC size and metastatic involvement of axillary LNs [40]. Similarly, the correlations in our LABC group also indicate that PET/CT parameters of the primary BC mass have prominent effect on the parameters of metastatic axillary LNs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, significant correlations between tumour size and the size of metastatic axillary LNs, SUV max -T and size of metastatic axillary LNs, SUV max -T and SUV max -LN were found in our LABC group. Primary tumour size was stated to be predictive of metastatic involvement of axillary LNs [33], SUV max -T was reported to increase with tumor grade [15, 17, 39] and strong relationships were found among SUV max values, BC size and metastatic involvement of axillary LNs [40]. Similarly, the correlations in our LABC group also indicate that PET/CT parameters of the primary BC mass have prominent effect on the parameters of metastatic axillary LNs.…”
Section: Discussionsupporting
confidence: 63%
“…Quantification of FDG uptake in breast tumors provide objective criteria to differentiate malignant tissue [38]. In recent years, several PET/CT studies have been performed to determine SUV max values of the primary tumour in BC patients, which is an important predictor of tumour behaviour [15,17,3941]. In a study including primary BC patients, researchers found that primary tumour FDG uptake (SUV max ) was significantly higher in tumours which had an unfavourable prognosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was indicated that FDG avidity of a breast cancer lesion depends on multiple factors [13]. One of these factors is the histological type of the tumor, where ILCs are known to have lower FDG avidity [14,15]. Although the number of patients in each of our histological subgroup was not identical, the SUVmax was significantly higher in IDC and IBC groups compared to ILC and IDC + ILC tumors.…”
Section: Discussionmentioning
confidence: 68%
“…Associations between SUV and clinicopathological features and immunohistochemical factors have been demonstrated in previous studies. Jung et al (2015) evaluated the associations between the maximum SUV (SUVmax) and prognostic factors in ILC, comparing these results with those in IDC. In particular, regarding the histological subtype they observed that the lowest mean SUV max was found among patients with ILCs in comparison with IDCs tumors.…”
Section: Correlation Between 18 F-fdg Pet/ct Results and Breast Cancementioning
confidence: 99%
“…Finally, both PR and HER-2 status did not indicate any significant difference given the SUV max uptake between ILCs and IDCs tumor groups. (Jung et al, 2015).…”
Section: Correlation Between 18 F-fdg Pet/ct Results and Breast Cancementioning
confidence: 99%